2020
DOI: 10.1016/j.enconman.2020.112663
|View full text |Cite
|
Sign up to set email alerts
|

Biomethane production using an integrated anaerobic digestion, gasification and CO2 biomethanation process in a real waste water treatment plant: A techno-economic assessment

Abstract: The biomethanation of CO 2 from anaerobic digestion within the power to gas concept has recently emerged as a promising technology to upgrade biogas, to decarbonise the domestic and industrial heat sector, provide long term energy storage and deliver grid balancing services. In addition, the utilisation of the digestate, through a process such as gasification, offers a circular economy approach and has the potential to enhance the deployment of power to gas systems. To this direction, the study focuses on expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 69 publications
(68 reference statements)
0
13
0
Order By: Relevance
“…Consequently, the difference between bSNG MSP and a base market price for a common alternative energy commodity, such as natural gas, can be estimated as in Eq. (12). Such price gap corresponds to the cost of achieving grid gas renewability through biomass-to-biomethane technologies.…”
Section: Minimum Selling Price Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the difference between bSNG MSP and a base market price for a common alternative energy commodity, such as natural gas, can be estimated as in Eq. (12). Such price gap corresponds to the cost of achieving grid gas renewability through biomass-to-biomethane technologies.…”
Section: Minimum Selling Price Estimationmentioning
confidence: 99%
“…Biomass gasification can thus be integrated with methanation and water electrolysis in PtG systems, with the potential to address fuel-type diversification and storage needs. Integrated biomass gasification and catalytic methanation systems have been widely studied from a modeling and system performance point of view [9], while only few studies so far have addressed the performance of integrated biomass gasification-biomethanation systems [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the characteristics of gasification, as well as the most important technologies, it can be concluded that sewage sludge gasification can play a key role in meeting the future needs of growing energy production. Gasifying sewage sludge or any biomass for clean energy production can provide sustainability a balanced reduction of greenhouse gas emissions and a steady energy supply [63], [64]. Consequently, sewage sludge and other biomass gasification deserve much attention because of the energy output in terms of quality and quantity.…”
Section: Conversion Of Domestic Sewage Sludge Using Thermochemical Processes: Gasification Combustionmentioning
confidence: 99%
“…For example, low-quality wood, agricultural biomass, sewage sludge, timber waste, or bio-waste could be converted to syngas consisting of CO, H 2 , CO 2 , CH 4 , N 2 and other components at the concentrations up to 0.2 vol% and consumed for heat and power production [1][2][3]. On the other hand, the obtained products are suitable for further conversion to bio-methane [4,5], hydrogen [6,7], or Fischer-Tropsch (F-T) synthesis [8]. However, the yield of the final product depends on the syngas composition, which in turn is closely related to the used feedstock, gasifying agent, temperature and gasifier design.…”
Section: Introductionmentioning
confidence: 99%